1985
DOI: 10.1007/bf00333428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin B12 and B6 on 2,5-hexanedione-induced neuropathy

Abstract: The therapeutic effect of Vitamin B12 or Vitamin B6 on 2,5-hexanedione induced-neuropathy in animals was examined by using our electrodiagnostic technique in order to investigate the mechanism of the development of the neuropathy. Pyridoxal phosphate and two forms of Vitamin B12 were administered to rats intoxicated by the neurotoxin for a period of 18 weeks, and the sensory and motor fiber conduction velocity and the motor distal latency of the tail nerve were periodically determined. None of the groups treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Alleviation of mechanical hyperalgesia in streptozotocin-induced diabetic rats by a mixture of vitamins B1, B6 and B12, or by vitamin B6 alone was associated with improved sensory nerve conduction velocity (Jolivalt et al, 2009), but no such change was found in rats rendered diabetic with 2,5-hexanedione and treated with vitamin B6 or B12 alone (Misumi et al, 1985). Other possible antihyperalgesic mechanisms of B vitamins include inhibition of the diacylglycerol-protein kinase C (PKC) pathway (Hammes et al, 2003;Sánchez-Ramírez et al, 2006), enhanced cGMP production by guanylylcyclase enzyme (Vesely, 1985) and increased afferent inhibitory control of nociceptive neurons at the spinal cord (Fu et al, 1998).…”
Section: Discussionmentioning
confidence: 89%
“…Alleviation of mechanical hyperalgesia in streptozotocin-induced diabetic rats by a mixture of vitamins B1, B6 and B12, or by vitamin B6 alone was associated with improved sensory nerve conduction velocity (Jolivalt et al, 2009), but no such change was found in rats rendered diabetic with 2,5-hexanedione and treated with vitamin B6 or B12 alone (Misumi et al, 1985). Other possible antihyperalgesic mechanisms of B vitamins include inhibition of the diacylglycerol-protein kinase C (PKC) pathway (Hammes et al, 2003;Sánchez-Ramírez et al, 2006), enhanced cGMP production by guanylylcyclase enzyme (Vesely, 1985) and increased afferent inhibitory control of nociceptive neurons at the spinal cord (Fu et al, 1998).…”
Section: Discussionmentioning
confidence: 89%
“…Previously, it has been reported that single or combined administration of thiamine, pyridoxine, and cyanocobalamin is able to reduce thermal hyperalgesia, but not mechanical allodynia, in dorsal root ganglion compression and CCI models [25] . In addition, Misumi et al [26] were not able to demonstrate an antiallodynic effect of either pyridoxine or cyanocobalamin on 2,5-hexanedione-induced neuropathy in rats. Differences could be due to the different way to induce neuropathy in the rats.…”
Section: Antiallodynic Effect Of B Vitamins and Dexamethasonementioning
confidence: 99%
“…Various studies have reported that 2,5-HO produces sensory deficits (Abou-Donia et al, 1985;Bastone et al, 1987;DiVicenzo et al, 1976;Fedtke & Bolt, 1987;Herskowitz et al, 1971;Misumi et al, 1985). Accordingly, animals treated with high doses of 2,5-HO should have been less sensitive to footshock than the animals in the vehicle group.…”
Section: Discussionmentioning
confidence: 97%